2020
DOI: 10.3390/ijerph17051656
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ghrelin Levels in Saudi Obese Asthmatic School-Children—Correlation with Interleukin-4, Interleukin-5, and Interleukin-21

Abstract: Ghrelin is a peptide hormone with direct or indirect effects on obesity and asthma. More data are required to understand the effect of ghrelin on the control and pathogenesis of these diseases. The aim of this study was to evaluate ghrelin levels in selected groups of children to identify the association between serum ghrelin, obesity, and the severity of asthma. The study included 401 school children selected from the Najran area and grouped into non-obese asthmatics, obese asthmatics, obese non-asthmatics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…In addition, Matsuda et al [247] described how ghrelin levels negatively correlated with IgE production, leading to the conclusion that ghrelin might inhibit directly or indirectly IgE synthesis. In contrast to the abovementioned research, Al-Ayed et al [248] found higher ghrelin levels in asthmatic children than in non-asthmatic ones. Moreover, subjects with uncontrolled asthma had higher ghrelin than patients with well-controlled disease.…”
Section: Stomach Peptide Ghrelinmentioning
confidence: 68%
“…In addition, Matsuda et al [247] described how ghrelin levels negatively correlated with IgE production, leading to the conclusion that ghrelin might inhibit directly or indirectly IgE synthesis. In contrast to the abovementioned research, Al-Ayed et al [248] found higher ghrelin levels in asthmatic children than in non-asthmatic ones. Moreover, subjects with uncontrolled asthma had higher ghrelin than patients with well-controlled disease.…”
Section: Stomach Peptide Ghrelinmentioning
confidence: 68%
“…[12,23]. Although S100B been linked to cerebral ischaemia, developing it into a biomarker for differential diagnosis in clinical practice has been problematic [24,25]. Several writers have claimed that elevated levels of S100B in the blood are not unique to stroke, claiming that the rise occurs in other neurological disorders with similar symptoms [26].…”
Section: Discussionmentioning
confidence: 99%
“…Our clinical interpretation of variant closely follows American College of Medical Genetics (ACMG) guideline. [5]. A distinctive pathology characterizes LD.…”
Section: Case Reportmentioning
confidence: 99%